Uterine artery embolization for uterine arterio-venous malformation - Sagili, Haritha; Krishnan, Nagarajan; Keepanasseril, Anish; Priya, Sathiya; Devaraj, Sunilkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Uterine arteriovenous malformations (AVM) as a cause of abnormal uterine bleeding are listed under “not otherwise classified” in Palm-Coein classification, is an abnormal communication between an artery and vein without an intervening capillary bed resulting in increased pressure and high velocity in the venous system. We report the case of heavy menstrual bleeding in a thirty-five-year-old primiparous lady for five years with fourteen weeks sized uterus and six gm hemoglobin. Ultrasound revealed an enlarged uterus with tubular spaces and color doppler showed tubular anechoic structures, both within the myometrium, with low resistance and high-velocity pattern suggestive of uterine arteriovenous malformations. Because of nonresponse to medical management, uterine artery embolization was carried out following which she had significant reduction in menstrual bleeding emphasizing it as a differential diagnosis in all cases presenting with heavy menses. Uterine artery embolization appears to be an effective modality of treatment especially in women whose wish to preserve fertility.